Dramatic and sustained responsiveness of pulmonary Langerhans cell histiocytosis-associated pulmonary hypertension to vasodilator therapy. (2015) - May, Adam; Kane, Garvan; Yi, Eunhee; Frantz, Robert; Vassallo, Robert
Abstract: Pulmonary Langerhans cell histiocytosis (PLCH) is an uncommon diffuse lung disease characterized by the abnormal accumulation of Langerhans' cells around small airways and other distal lung compartments. Although pulmonary hypertension (PH) is a frequent complication of PLCH, the role of advanced PH therapies for PLCH-related PH is not well-established. We describe a PLCH patient with severe, disease-related PH that responded unexpectedly well to advanced PH therapy with sustained improvement over a 10 year follow-up period. This case indicates that PLCH-associated PH may, in certain instances, be highly responsive to advanced PH therapies and emphasizes the importance of trialing these therapies among patients with PLCH-related PH.